Analysis of a multiple-porosity model for single-phase flow through naturally fractured porous media - Anna Maria Spagnuolo; Steve Wright (Journal of Applied Mathematics)
A derivation of a multiple-porosity model for the flow of a single phase, slightly compressible fluid in a multiscale, naturally fractured reservoir is presented by means of recursive use of homagnetization theory. We obtain a model which generalizes the double-porosity model of Arbogast et al. (1990) to a flow system with an arbitrary finite number of scales.